Antisemitism - Schweitzer, F. author. aut Link
X, 309 p.
Keywords: In this provocative book, Marvin Perry and Frederick M. Schweitzer analyze the lies, misperceptions, and myths about Jews and Judaism that anti-semites have propagated throughout the centuries. Beginning with antiquity, and continuing into the present day, the authors explore the irrational fabrications that have led to numerous acts of violence and hatred against Jews. The book examines ancient and medieval myths central to the history of anti-semitism: Jews as 'Christ-killers', instruments of Satan, and ritual murderers of Christian children. It also explores the scapegoating of Jews in the modern world as conspirators bent on world domination; extortionists who manufactured the Holocaust as a hoax designed to gain reparation payments from Germany; and the leaders of the slave trade that put Africa in chains. No other book has focused its attention exclusively on a thematic discussion of historic and contemporary anti-semitic myths, covering such an expansive scope of time, and allowing for such a painstaking level of exemplification. Anti-semitism is an essential book that will serve as a corrective to bigotry, stereotype, and historical distortion.